A rapid qualitative methods assessment and reporting tool for epidemic response as the outcome of a rapid review and expert consultation. - Dong Dong; Sharon Abramowitz; Gustavo Corrêa Matta; Arlinda B Moreno; Elysée Nouvet; Jeni Stolow; Caitlin Pilbeam; Shelley Lees; E K Yeoh; Nina Gobat; Tamara Giles-Vernick (PLOS Global Public Health)
During the first year of the COVID-19 pandemic, the Methods Sub-Group of the WHO COVID-19 Social Science Research Roadmap Working Group conducted a rapid evidence review of rapid qualitative methods (RQMs) used during epidemics. The rapid review objectives were to (1) synthesize the development, implementation, and uses of RQMs, including the data collection tools, research questions, research capacities, analytical approaches, and strategies used to speed up data collection and analysis in their specific epidemic and institutional contexts; and (2) propose a tool for assessing and reporting RQMs in epidemics emergencies. The rapid review covered published RQMs used in articles and unpublished reports produced between 2015 and 2021 in five languages (English, Mandarin, French, Portuguese, and Spanish). We searched multiple databases in these five languages between December 2020 and January 31, 2021. Sources employing "rapid" (under 6 months from conception to reporting of results) qualitative methods for research related to epidemic emergencies were included. We included 126 published and unpublished sources, which were reviewed, coded, and classified by the research team. Intercoder reliability was found to be acceptable (Krippendorff's α = 0.709). We employed thematic analysis to identify categories characterizing RQMs in epidemic emergencies. The review protocol was registered at PROSPERO (no. CRD42020223283) and Research Registry (no. reviewregistry1044). We developed an assessment and reporting tool of 13 criteria in three domains, to document RQMs used in response to epidemic emergencies. These include I. Design and Development (i. time frame, ii. Training, iii. Applicability to other populations, iv. Applicability to low resource settings, v. community engagement, vi. Available resources, vii. Ethical approvals, viii. Vulnerability, ix. Tool selection); II. Data Collection and Analysis (x. concurrent data collection and analysis, xi. Targeted populations and recruitment procedures); III. Restitution and Dissemination (xii. Restitution and dissemination of findings, xiii. Impact). Our rapid review and evaluation found a wide range of feasible and highly effective tools, analytical approaches and timely operational insights and recommendations during epidemic emergencies.